Urgensi Penerapan Kebijakan Cukai atas Minuman Berpemanis Dalam Kemasan (MBDK) di Indonesia - Siregar, Padian Adi Salamat (ETHNOGRAPHY: Journal of Design, Social Sciences and Humanistic Studies, 2025)
This study aims to see how the application of sweetened beverage excise can be an effective policy instrument in controlling the consumption of sugary drinks and reducing adverse health impacts on people in Indonesia. This study uses a systematic review approach by analyzing various literature and data related to the sweetened beverage excise policy and its impact on public health. Data was collected from a variety of primary and secondary sources, including scientific journal articles, government reports, case studies of policy implementation in different countries, and health survey data. Data analysis was carried out qualitatively by identifying the main themes related to health impacts, health burdens, and the effectiveness of the implementation of sweetened beverage excise policies in various countries. The results of the analysis show that the optimal excise tariff structure for sweetened beverages can be applied based on the sweetener content in the product. A progressive approach, in which excise rates increase in line with rising sugar levels in beverages, could be an option. For example, drinks with a sugar content of less than 5 grams per 100 ml can be exempt from excise, while drinks with a sugar content between 5 and 10 grams are subject to low tariffs, and products with a sugar content of more than 10 grams are subject to higher tariffs. A mechanism for periodic tariff adjustments is also important to ensure that these policies remain relevant and effective.